Influence of phosphorus application on growth and yield of soybean genotypes in the tropical savannas of northeast Nigeria - Kamara, A.Y.; Abaidoo, Robert C.; Kwari, J.; Omoigui, L.O. (Informa UK Limited, 2007)
The cultivation of soybean is increasing in the savannas of Nigeria due to its widespread use in the food and feed industry. Production is, however, constrained by low soil phosphorus (P) levels in northeast Nigeria. This study evaluated four soybean varieties for their response to three rates of P in two agro-ecozones in 2004 and 2005. Experimental design was a split-plot arrangement of treatments with three replications. The main plots were assigned the P treatments and subplots were soybean cultivars randomised within the main plots. The studies found that soybean responds to P application but differences between 20 and 40 kg Pha were not significant, despite low test P levels. This may be due to limitations in other nutrients. More studies are needed to determine the synergistic effect of P and other nutrients on soybean growth and yield. Soybean growth and seed yield were lower in 2004 than in 2005 because trials were established comparatively late in 2004 and crops were therefore affected by late season moisture stress. There is, therefore, a need to establish the appropriate time for planting soybean in these zones. Late maturing varieties produced higher yields than early maturing varieties in 2005 probably due to early planting which allowed full use of the growing season.